Studies of the Selective Removal of Microquantities of Platinum(IV) Ions from Model Chloride Solutions onto Ion Exchangers Containing Functional Tertiary Amine and Polyamine Groups - Z. Hubicki; G. Wójcik (Adsorption Science & Technology)
Since platinum is applied widely in industry, the recovery of noble metals from industrial wastes becomes an economic issue. Laboratory studies have been undertaken of the selective removal of microquantities of Pt(IV) ions from 0.1–6 M hydrochloric acid solutions onto ion exchangers containing functional tertiary amine groups (Amberlite IRA-67 and Amberlite IRA-93) or functional polyamine groups (Diaion CR 20). The recovery factor values [% R Pt(IV)] were determined for these ion exchangers as well as the sorption isotherms which depended on the kind of aqueous phase employed and the phase contact time. In addition, the weight and volume distribution coefficients, the number of theoretical plates as well as the working ion-exchange capacities were calculated from the Pt(IV) ion breakthrough curves. Due to their high ion-exchange capacities relative to Pt(IV) ions and their high resistance towards chemical agents, these ion exchangers may be applied both in platinum recovery technologies and in analysis of trace amounts of the noble metal.